1986
DOI: 10.1007/bf01314289
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a herpes simplex virus regulatory protein: Aggregation and phosphorylation of a temperature-sensitive variant of ICP 4

Abstract: The viral polypeptide ICP 4 (or Vmw 175) is synthesized during the immediate early phase of infection by herpes simplex virus (HSV) and is required during the viral reproductive cycle for efficient transcription of delayed early viral genes. Replication of mutant strains of HSV-1 such as tsLB 2 that encode a temperature-sensitive variant of ICP 4 does not proceed beyond the immediate early phase in cells that are infected and maintained at the nonpermissive temperature (NPT). Under these conditions, the immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…However, an in-frame deletion mutant from which residues 185 to 309 have been removed can be phosphorylated (DeLuca & Schaffer, 1988). This suggests that either the six remaining serine residues between 176 and 184 can be phosphorylated in the absence of the rest of the conserved region, or that other sites in the protein (including threonine residues; Faber & Wilcox, 1986a) are also targets for phosphorylation. Whatever the role of this conserved sequence in the phosphorylation of Vmw175, it is very surprising that it is not essential for the function of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an in-frame deletion mutant from which residues 185 to 309 have been removed can be phosphorylated (DeLuca & Schaffer, 1988). This suggests that either the six remaining serine residues between 176 and 184 can be phosphorylated in the absence of the rest of the conserved region, or that other sites in the protein (including threonine residues; Faber & Wilcox, 1986a) are also targets for phosphorylation. Whatever the role of this conserved sequence in the phosphorylation of Vmw175, it is very surprising that it is not essential for the function of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…It is a phosphorylated nuclear DNAbinding protein with an apparent Mr of 175K in SDSpolyacrylamide gels, and can be poly(ADP-ribosyl)ated in isolated nuclei (Powell & Purifoy, 1976;Pereira et al, 1977;Cabral et al, 1980;Hay & Hay, 1980;Preston & Notarianni, 1983). Phosphorylation of Vmw175 occurs at both serine and threonine residues (Faber & Wilcox, 1986a) and as pulse-chase experiments have indicated that phosphate groups can cycle on and off the polypeptide during infection (Wilcox et al, 1980) it is possible that phosphorylation plays some role in its regulatory activities. Vmw175 can be isolated in multimeric (principally dimeric) forms (Metzler & Wilcox, 1985) and has been purified almost to homogeneity (Kattar-Cooley & Wilcox, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of phosphorylation of ICP4 has been shown to affect its DNA-binding properties (39) and potentially its interaction with cellular proteinviral DNA complexes (41). Both serine and threonine residues were found to be phosphorylated in a temperature-sensitive mutant form of ICP4 labeled at the nonpermissive temperature (15). ICP4 can also be ADP-ribosylated (49) or adenylated and guanylated (2) in isolated nuclei, yet the significance of this observation in regard to infected cells has not been established.…”
mentioning
confidence: 99%
“…Ts mutants of herpes simplex virus (HSV) have been generated or found in the laboratory and reported to have a mutation in UL36 of HSV-1 [2], ICP4 of HSV-1 [3][4][5][6][7][8], UL15 of HSV-1 [9], HSV-1 protease of HSV-1 [10], UL9 of HSV-1 [11], UL28 of HSV-1 [12], gB of HSV-1 [3,13], ribonucleotide reductase (RR) large subunit of HSV-1 [14,15] and HSV-2 [15] and small subunit of HSV-1 [14,16], UL11 of HSV-1 [17], Vmw65 of HSV-1 [18], ICP27 of HSV-1 [19], ICP8 of HSV-1 [6], DNA polymerase [6], and virion-associated host shutoff protein [20]. Thus, ts mutants have been analyzed to understand their gene functions, but all mutants examined were laboratory strains, making it difficult to predict the location of the This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%